qPCR detection of Mycobacterium leprae DNA in urine samples of leprosy patients using the Rlep gene target - Diana, D.; Harish, M. C. (Frontiers in Molecular Biosciences, 2024)
Leprosy, a chronic infectious disease caused by Mycobacterium leprae, continues to pose a public health challenge in many parts of the world. Early and accurate diagnosis is crucial for effective treatment and prevention of disabilities associated with the disease. Molecular techniques such as polymerase chain reaction have demonstrated great potential as a diagnostic tool for directly detecting M.leprae DNA in different clinical samples, providing better sensitivity and specificity than conventional diagnostic techniques. The objective of this study was to measure the amount of M.leprae DNA in leprosy patients' urine samples using Rlep gene target through qPCR.Different clinical samples such as smear, blood, and urine samples were collected from leprosy patients and healthy individuals. Leprosy patients were classified by Ridley-Jopling classification. Ziehl-Neelsen (ZN) staining method was used for SSS samples and Bacteriological Index (BI) was calculated for leprosy patients. DNA extraction and qPCR was performed for all three clinical samples using Rlep gene target.The Mycobacterial leprae DNA was successfully detected and quantified in all clinical samples across all types of leprosy among all the study groups using Rlep gene (129 bp) target. Rlep gene target was able to detect the presence of M.leprae DNA in 100 % of urine, 96.1 % of blood, and 92.2 % of SSS samples of leprosy patients.Urine samples showed significance differences (p<0.001) between control and the different clinical forms, and between BT and PNL. There are significant differences in Ct values between control cases and clinical categories (p<0.001), as well as specific differences within clinical categories (p<0.001), reflecting the variability in bacterial load and detection sensitivity across different sample types and clinical manifestations of leprosy.Overall, this study findings suggests that qPCR technique can be used for the detection of M.leprae DNA in urine samples of leprosy patients using Rlep gene target and can be used for both diagnosing and monitoring the effectiveness of anti-leprosy drugs including MDT across various leprosy disease group.